The first Japanese nationwide multicenter study of BRCA mutation testing in ovarian cancer: CHARacterizing the cross-sectionaL approach to Ovarian cancer geneTic TEsting of BRCA (CHARLOTTE). Issue 6 (July 2019) - Enomoto, Takayuki; Aoki, Daisuke; Hattori, Kana; Jinushi, Masahisa; Kigawa, Junzo; Takeshima, Nobuhiro; Tsuda, Hitoshi; Watanabe, Yoh; Yoshihara, Kosuke; Sugiyama, Toru
Abstract : Introduction: BRCA gene mutations are associated with hereditary ovarian cancer. BRCA plays a key role in genome integrity, and mutations result in an increased risk for ovarian cancer. Although various guidelines recommend BRCA testing in patients with ovarian cancer, data on germline BRCA (g B RCA ) mutation frequency in ovarian cancer in Japan are scarce. Objective: This study aimed to determine g BRCA1/2 mutations in Japanese patients with ovarian cancer, stratified by clinicopathological characteristics, and to assess patients' satisfaction with pre-test genetic counseling. Methods: The CHARLOTTE study (CHARacterizing the cross-sectionaL approach to Ovarian cancer: geneTic TEsting of BRCA ; UMIN000025597) is the first large multicenter epidemiological survey of Japanese women, aged ≥20, with newly diagnosed ovarian cancer (epithelial, primary peritoneal, or fallopian tube cancer), with histologically confirmed specimens. Patients were enrolled sequentially and underwent pre-test genetic counseling for BRCA testing. Blood samples were centrally tested for the presence or absence of known g BRCA mutations. A questionnaire was used to assess patient satisfaction with pre-test genetic counseling. Results: A total of 634 patients with a mean age of 56.9 years were included. Most patients (84.2%) had epithelial ovarian cancer, and 51.1% had FIGO stage III–IV cancer. Nearly all patients (99.5%) received genetic counseling before the BRCA testing, either by an obstetrician-gynecologist (42.0%) or a clinical geneticist (42.0%). The overall prevalence of g BRCA1/2 mutations was 14.7% (93/634), with g BRCA1 mutations (9.9%) more common than g BRCA2 mutations (4.7%). High-grade serous carcinoma showed a prevalence of g BRCA mutations of 28.5%. Most patients were satisfied with pre-test counseling, irrespective of the service provider's professional position. Discussion: Patients with high-grade serous carcinoma and family history of ovarian cancer had a slightly higher prevalence of g BRCA mutations, but none of the subgroups had considerably high g BRCA mutation prevalence. These data suggest that g BRCA testing should be carried out in all patients with ovarian cancer.